Recontextualizing Maqasid al-Shariah in Contemporary Qur’anic Exegesis: A Comparative Study of Jasser Auda and Classical Scholars - Sulhadi, Asep (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2024)
This study explores the recontextualization of Maqāṣid al-Sharī‘ah in contemporary Qur’anic exegesis, contrasting the methodologies of modern scholar Jasser Auda with those of classical commentators. At its core, Maqāṣid emphasizes the ethical objectives of Islamic law—initially preservation of faith, life, intellect, lineage, and property. Modern scholars like Auda have argued for expanding this framework into social, economic, and environmental domains using a systems approach—integrating six features: cognition, wholeness, openness, interrelated hierarchy, multidimensionality, and purposefulness. Classical tafsīr, rooted in textual and juridical reasoning, often treats legal objectives narrowly and atomistically. This paper identifies a methodological shift: Auda reconceptualizes Maqāṣid not merely as interpretive background but as hermeneutical lens, facilitating thematic Qur’anic reading, resolution of legal contradictions, and contextual adaptation. Through comparative analysis, we map how this shift impacts interpretation of legal verses, engages modern concerns—such as human rights and societal development—and dialogues with classical sensitivity. Findings reveal that Auda’s systems-based Maqāṣid enriches contemporary Qur’anic exegesis by promoting a more holistic, justice-oriented, and contextualized interpretive framework. This research contributes to Qur’anic studies and Islamic legal hermeneutics by demonstrating how Maqāṣid can bridge classical sources and modern exigencies, thereby revitalizing Qur’anic interpretation for the 21st century.